Organoids and spheroids: advanced in vitro models for liver cancer research - Mirella Pastore; Alessia Giachi; Elena Spínola-Lasso; Fabio Marra; Chiara Raggi (Frontiers in Cell and Developmental Biology)
Liver cancer is a leading cause of cancer-related deaths worldwide, highlighting the need for innovative approaches to understand its complex biology and develop effective treatments. While traditional in vivo animal models have played a vital role in liver cancer research, ethical concerns and the demand for more human-relevant systems have driven the development of advanced in vitro models. Spheroids and organoids have emerged as powerful tools due to their ability to replicate tumor microenvironment and facilitate preclinical drug development. Spheroids are simpler 3D culture models that partially recreate tumor structure and cell interactions. They can be used for drug penetration studies and high-throughput screening. Organoids derived from stem cells or patient tissues that accurately emulate the complexity and functionality of liver tissue. They can be generated from pluripotent and adult stem cells, as well as from liver tumor specimens, providing personalized models for studying tumor behavior and drug responses. Liver organoids retain the genetic variability of the original tumor and offer a robust platform for high-throughput drug screening and personalized treatment strategies. However, both organoids and spheroids have limitations, such as the absence of functional vasculature and immune components, which are essential for tumor growth and therapeutic responses. The field of preclinical modeling is evolving, with ongoing efforts to develop more predictive and personalized models that reflect the complexities of human liver cancer. By integrating these advanced in vitro tools, researchers can gain deeper insights into liver cancer biology and accelerate the development of novel treatments.